Extra - Deutsch, David; Lloyd, Seth; Nickas, Bob; Tupper, Martin; Wahler, Marc-Olivier (New York : Swiss Institute - Contemporary Art, 2003)
Barré, Virginie ; Blanckart, Olivier ; Breuning, Olaf ; Dafflon, Stéphane ; Delvoye, Wim ; Deutsch, David ; Firman, Daniel ; Fischer, Urs ; Fischli & Weiss ; Fischli, Peter ; Fleury, Sylvie ; Gelatin ; Giorno, John ; Gordon, Janine ; Gygi, Fabrice ; Hersberger, Lori ; Jankowski, Christian ; Koether, Jutta ; Lloyd, Seth ; Mosset, Olivier ; Motti, Gianni ; Nickas, Bob ; Parker, Erik ; Parrino, Steven ; Peinado, Bruno ; Rondinone, Ugo ; Ruggirello, Jean-Claude ; Sautour, Stéphane ; Shaw, Jim ; Signer, Roman ; Tupper, Martin ; Weiss, David ; Westphalen, Olav ; Wurm, Erwin
Extra, Swiss Institute - Contemporary Art New York, 2003-03-05. 2003-04-26
boek